2012
DOI: 10.1161/strokeaha.111.638403
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Lack of Development of Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-Patients with aneurysmal subarachnoid hemorrhage are typically kept in the intensive care unit to be monitored for signs of delayed cerebral ischemia (DCI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 33 publications
5
39
0
Order By: Relevance
“…A recent study found exactly the same predictors (good clinical condition on admission, small amounts of extravasated blood, and older age) to be associated with a low risk of DCI. 8 However, because the authors chose to predict 100% absence of *Both models are after adjustment for overfitting by shrinkage (regression coefficients were shrunk by 16% in the first model, and 21% in the second model).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found exactly the same predictors (good clinical condition on admission, small amounts of extravasated blood, and older age) to be associated with a low risk of DCI. 8 However, because the authors chose to predict 100% absence of *Both models are after adjustment for overfitting by shrinkage (regression coefficients were shrunk by 16% in the first model, and 21% in the second model).…”
Section: Discussionmentioning
confidence: 99%
“…5 Previous prediction models for DCI after SAH are impractical in daily practice or not confined to data present at admission, and most are not validated. [6][7][8] Furthermore, a risk prediction chart does not exist.…”
mentioning
confidence: 99%
“…24 The VASOGRADE derived from the studies published by de Rooij et al 15 and Crobeddu et al, 16 who developed risk charts to predict who would or would not develop DCI, respectively, combining the WFNS 9 and the modified Fisher scales.…”
Section: Discussionmentioning
confidence: 99%
“…The main idea was to create an ease-to-remember, ease-to-use, and practical grading system that would allow clinicians to tailor monitoring strategies and treatment aggressiveness according to the different grades. The VASOGRADE derived from previously published studies by de Rooij et al 15 and Crobeddu et al, 16 which showed clinical condition on admission and the amount of blood on CT (associated with age), as the major risk factors for DCI and DCI-related cerebral infarction. This analysis represents, therefore, the external validation of de Rooij et al, 15 in a large and diverse sample of SAH patients.…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation